2018
DOI: 10.1158/0008-5472.can-17-3341
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively-Activated Macrophages Upregulate Mesothelial Expression of P-Selectin to Enhance Adhesion of Ovarian Cancer Cells

Abstract: Peritoneal metastasis of high-grade serous ovarian cancer (HGSOC) occurs when tumor cells suspended in ascites adhere to mesothelial cells. Despite the strong relationship between metastatic burden and prognosis in HGSOC, there are currently no therapies specifically targeting the metastatic process. We utilized a coculture model and multivariate analysis to examine how interactions between tumor cells, mesothelial cells, and alternatively-activated macrophages (AAM) influence the adhesion of tumor cells to me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 47 publications
2
56
1
1
Order By: Relevance
“…The elevated EGFR, in tumors, further activates the VEGF/VEGFR pathway in neighboring tumor cells, and thus supports cell proliferation and metastasis. M2-like macrophages facilitate the cell adhesion of ovarian cancer cells to mesothelial cells by causing the mesothelial cells to over-express P-selectin [ 35 ]. This mechanism likely supports the epithelial ovarian cancer spread, along the mesothelial-lined peritoneal cavity.…”
Section: Bipolar Macrophagesmentioning
confidence: 99%
“…The elevated EGFR, in tumors, further activates the VEGF/VEGFR pathway in neighboring tumor cells, and thus supports cell proliferation and metastasis. M2-like macrophages facilitate the cell adhesion of ovarian cancer cells to mesothelial cells by causing the mesothelial cells to over-express P-selectin [ 35 ]. This mechanism likely supports the epithelial ovarian cancer spread, along the mesothelial-lined peritoneal cavity.…”
Section: Bipolar Macrophagesmentioning
confidence: 99%
“…The activation of apoptosis is regulated by multiple signalling pathways, of which the PI3K/AKT pathway is one of the most important (20). The PI3K/AKT pathway regulates a number of malignant phenotypes, including anti-apoptotic, cell growth and proliferation phenotypes (21,22). In this pathway, AKT activation inhibits cell cycle arrest and angiogenesis, and promotes tumour invasion and metastasis via phosphorylation of the protein kinase mTOR (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…For some experiments, HGSOC cells were cultured on coverslips in the device without monocytes. AAM control monocultures were generated as previously described (16).…”
Section: In Vitro Micro-culture Devicementioning
confidence: 99%
“…In vivo, a resident population of omental CD163+ macrophages has been shown to be essential for metastatic spread in a mouse model of ovarian cancer (15). Using in vitro models of HGSOC, we have previously demonstrated that AAMs secrete soluble factors such as MIP-1, HB-EGF, and leptin, resulting in increased ovarian cancer adhesion, proliferation, and spreading, respectively (16)(17)(18). In these studies, AAMs were generated by differentiating naïve monocytes into macrophages with MCSF and then polarizing towards the alternative phenotype through IL-4…”
Section: Introductionmentioning
confidence: 99%